Development of numerical algorithm to guide solder joint structure and component structural design during manufacturing. (April 2017) - Chen, Yilong; Jia, Jianyuan; Fu, Hongzhi; Zhu, Zhaofei
Abstract: In order to improve the production technology of the lead-free BGA (Ball Grid Array) assembly, a numerical method is developed to predict the yield of the soldering process based on calculated stand-off stiffness curves and component warpage. The stand-off stiffness curve which reflects the relationship of the force and height of solder joints is obtained by solving the differential equations of the solder joint shapes of BGA solder joints using the Runge-Kutta method. The analytical expression of thermal warpage of component in free boundary constraint conditions is proposed based on the lamination theory of the elastic mechanics. The expression can reflect the material parameter variation with temperature and provide an effective calculation method to analyze component warpage with large changing temperature during soldering reflow process. Considering the manufacture deviation of volumes and the randomness of the positions of the solder joints, combined with the stand-off stiffness curves and the component warping deformation, the yield of the soldering process can be predicted. According to the types and positions of the failure solder joints, the production technology can be improved. Based on the stand-off curves of solder joints, the influence of the deviation rate of volume of the solder joint and diameter of pad on the yield of self-assembly are simulated. The optimal matching relations of the solder joint volume and the diameter of the pad with the 0.35 mm pitch and 0.3 mm pitch are analyzed. Highlights: A numerical method is developed to predict the yield of the soldering process. The common region of the stand-off stiffness curves determines the yield. Decreasing the deviation rate of solder joints volume can improve the yield. The yield can be improved with the decreasing diameter of pad. Processing parameters of 0.35 mm and 0.3 mm pitch packages are predicted.